Differences of simulated ankle dorsiflexion limitation on lower extremity biomechanics during long jump takeoff - Zanni Zhang; Datao Xu; Xiangli Gao; Huiyu Zhou; Julien S. Baker; Zsolt Radak; Yaodong Gu (Heliyon)
The long jump is an athletic event that demands speed, power, force application, and balance, with each phase being critical to overall performance. However, previous research has neglected the limiting effect of the wedge pedals on ankle dorsiflexion range of motion. This cross-sectional study investigated biomechanical changes in the lower extremities during long jumps under varying degrees of ankle dorsiflexion. Thirty male Division II long jump athletes executed jumps under three conditions: no dorsiflexion, with 10° dorsiflexion restriction, and with 20° dorsiflexion restriction. A Vicon motion capture system with eight cameras and an AMTI force platform were used to collect biomechanical data simultaneously during the long jump. The angles, moments, and velocities of the ankle, hip, and knee joints during takeoff were simulated and calculated using a musculoskeletal model. Between-group variations were assessed using one-way repeated measures ANOVA, with statistical parametric mapping (SPM1D) applied for analysis. Results showed that as ankle restriction increased, vertical velocity gain increased: NW (3.34 ± 0.21 m/s), 10W (3.65 ± 0.14 m/s), and 20W (3.77 ± 0.12 m/s) (p < 0.001). Horizontal velocity loss was significantly higher only at 20W (p = 0.002). Peak extension angle, angular velocity, and power were highest at 10W for the knee and hip joints (p < 0.05). Joint forces at the ankle, knee, and hip were significantly affected by different pedal angles (p < 0.001). Athletes with a 10° ankle dorsiflexion limit showed increased vertical velocity with minimal horizontal velocity loss, potentially enhancing performance. This limit also increased muscle co-activation around the knee, possibly stabilizing it. Athletes should consider a 10° ankle dorsiflexion limit in training to improve performance and reduce injury risk.